Physical and mental health outcomes following housing improvements: evidence from the GoWell study. Issue 1 (9th September 2014) - Curl, Angela; Kearns, Ade; Mason, Phil; Egan, Matthew; Tannahill, Carol; Ellaway, Anne
Abstract : Background: Existing research points towards physical and mental health gains from housing improvements, but findings are inconsistent and often not statistically significant. The detailed characteristics and variability of housing improvement works are problematic and studies are often small, not experimental, with short follow-up times. Methods: A quasi-experimental design was used to assess the impact on physical health and mental health (using SF-12v2 Physical and Mental health component summary scales) of four types of housing improvement works—central heating, 'Secured By Design' front doors, fabric works, kitchens and bathrooms—both singly and in pairwise combinations. A longitudinal sample of 1933 residents from 15 deprived communities in Glasgow, UK was constructed from surveys carried out in 2006, 2008 and 2011. Sociodemographic characteristics and changes in employment status were taken into account. Results: Fabric works had positive associations with physical health (+2.09, 95% CI 0.13 to 4.04) and mental health (+1.84, 95% CI 0.04 to 3.65) in 1–2 years. Kitchens and bathrooms had a positive association with mental health in 1–2 years (+2.58, 95% CI 0.79 to 4.36). Central heating had a negative association with physical health (−2.21, 95% CI −3.74 to −0.68). New front doors had a positive association with mental health in <1 year (+5.89, 95% CI 0.65 to 11.14) and when provided alongside kitchens and bathrooms (+4.25, 95% CI 1.71 to 6.80). Gaining employment had strong associations with physical health (+7.14, 95% CI 4.72 to 9.55) as well as mental health (+5.50, 95% CI 3.27 to 7.73). Conclusions: Fabric works may provide insulation benefits and visual amenity benefits to residents. Front doors may provide important security benefits in deprived communities. Economic regeneration is important alongside property-led regeneration.